The saNeuroGut Initiative: Investigating the Gut Microbiome and Symptoms of Anxiety, Depression, and Posttraumatic Stress - Michaela A. O'Hare; Patricia C. Swart; Stefanie Malan-Müller; Leigh L. van den Heuvel; Erine Bröcker; Soraya Seedat; Sian M.J. Hemmings (Neuroimmunomodulation)
Introduction: Common mental disorders, such as anxiety disorders, depression, and posttraumatic stress disorder (PTSD), present a substantial health and economic burden. The gut microbiome has been associated with these psychiatric disorders via the microbiome-gut-brain axis. However, previous studies have focused on the associations between the gut microbiome and common mental disorders in European, North American, and Asian populations. As part of the saNeuroGut Initiative, we assessed associations between gut microbial composition and self-reported symptoms of anxiety, depression, and posttraumatic stress (PTS) among South African adults. Methods: Participants completed validated, online self-report questionnaires to evaluate symptoms of state anxiety, trait anxiety, depression, and PTSD. Eighty-six stool-derived microbial DNA samples underwent sequencing of the V4 region of the 16S rRNA gene to characterise gut bacterial taxa in the sample. Results: No significant associations were observed between symptom severity scores and alpha (Shannon and Simpson indices) and beta (Aitchison distances) diversity metrics. Linear regression models revealed that the abundances of Catenibacterium, Collinsella, and Holdemanella were significantly positively associated with the severity of PTS symptoms. Conclusion: Catenibacterium, Collinsella, and Holdemanella have each previously been associated with various psychiatric disorders, with Catenibacterium having been positively associated with symptoms of PTSD in another South African cohort. This study sheds light on the relationship between the human gut microbiome and symptoms of anxiety, depression, and PTS in a South African adult sample.